2021
DOI: 10.1017/s147895152100136x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the validity and reliability of the Turkish version of the Functional Assessment of Cancer Therapy—Cognitive Function in cancer patients

Abstract: Objective The Functional Assessment of Cancer Therapy—Cognitive Function (FACT-Cog) is a questionnaire that is used to evaluate the quality of life and cognitive functions according to individual self-reports. The aim of this study was to investigate the validity and reliability of the Turkish version of the FACT-Cog. Methods Cancer patients who were treated with chemo or radiotherapy and had a score of 24/30 and more in Mini-Mental State Examination (MMSE) were included in this study. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The FACT-COG Questionnaire, which is used for cognitive functions, is lled out by the patient by evaluating chemotherapy-induced behavioral cognitive impairment and its treatment, with questions about the last 7 days. This questionnaire evaluates parameters such as attention and coordination, memory, cognitive function, verbal uency, functional complexity (interference), quality of life, observations of others about the individual, and changes in functionality compared to before [12].…”
Section: Methodsmentioning
confidence: 99%
“…The FACT-COG Questionnaire, which is used for cognitive functions, is lled out by the patient by evaluating chemotherapy-induced behavioral cognitive impairment and its treatment, with questions about the last 7 days. This questionnaire evaluates parameters such as attention and coordination, memory, cognitive function, verbal uency, functional complexity (interference), quality of life, observations of others about the individual, and changes in functionality compared to before [12].…”
Section: Methodsmentioning
confidence: 99%
“…The FACT-Cog-v3 is a relatively brief measure and seems to be one of the most promising self-report instruments to evaluate these specific concerns, incorporating multiple dimensions such as perceived cognitive impairments (CogPCI), comments from others (CogOth), perceived cognitive abilities (CogPCA), and impact on quality of life (CogQoL). This scale was originally developed in English [ 7 ] and has been widely administered across clinical settings and validated across different cultures and languages, including French [ 14 ], Chinese [ 15 ], Korean [ 16 ], Japanese [ 17 ], Turkish [ 18 ], and English [ 9 , 19 ]. These validation studies have shown good psychometric qualities, including reliability, validity, and demonstration of cross-cultural adequacy.…”
Section: Introductionmentioning
confidence: 99%